Yoga for stress reduction and injury prevention at work. - Gura ST (Work, 2002)
At work employees face numerous psychological stressors that can undermine their work performance. These stressors, stemming from a variety of possible causes, have enormous health and financial impacts on employees as well as employers. Stress has been shown to be one of the factors leading to musculo-skeletal disorders (MSDs) such as: include back pain, carpal tunnel syndrome, shoulder or neck tension, eye strain, or headaches. Yoga is an ancient form of exercise that can reduce stress and relieve muscular tension or pain. Practicing yoga at the workplace teaches employees to use relaxation techniques to reduce stress and risks of injury on the job. Yoga at the workplace is a convenient and practical outlet that improves work performance by relieving tension and job stress.